PENGEMBANGAN KIT PROYEK STEM SUHU DAN KALOR UNTUK MELATIH KEMAMPUAN SAINTIFIK DALAM PEMBELAJARAN SAINS SISWA SLTP - Farhan, M. Refqi; Z. Zulirfan, Z. Zulirfan; M. Rahmad, M. Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: To improve the quality of learning, teachers can use various media, for example by using the IPA KIT. The use of the IPA KIT Media in science learning is very important, considering that Science is one of the subjects in the science family. The STEM project KIT in this study was developed on the material of Temperature and Heat for junior high school students' science learning. The purpose of this study was to produce a unit of the STEM Project KIT on temperature and heat material which is valid as a medium for learning science for junior high schools. This research is expected that students can gain an understanding of a concept of a lesson by learning physics and not feel bored because of the memorable learning process. This type of research is Research and Development (R&D) using the ADDIE model. This research is only limited to the development stage. The research instrument used in this study was the KIT validation assessment sheet and the guidelines used by the validator to assess the appropriateness of using the temperature and heat STEM projection KIT for teaching and learning activities to improve students' scientific abilities. Data analysis in this study used quantitative data analysis, by calculating the average validity score of each validity indicator. The results showed that the Temperature and Heat STEM Project KIT was declared valid with the overall score for the Temperature and Heat STEM Project KIT was 3.46 with very valid criteria, and for the KIT Guidelines for the Temperature and Heat STEM Project got an overall score of 3,55 with very valid criteriaKeywords: KIT , STEM Project, Scientific skills, Temperature and Heat